Pengaruh Kepemimpinan Islami Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada Pt. Bank Syariah Mandiri, Tbk Kantor Cabang Pembantu Sukaramai Medan - Sunarji Harahap (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2016)
This study aims to determine how much influence the Islamic leadership and work motivation on employee performance. The research was conducted at PT. Bank Syariah Mandiri, Tbk Branch Office Sukaramai Medan, the number of 21 people. Islamic leadership and motivation within the company is essential that all work can be done well and efficiently. Data collection techniques used is to use a questionnaire / questionnaire given to each respondent. Technical analysis of the data used is multiple linear regression, with the formula Y = a + b1x1 + b2X2 + e, and to determine how much influence the Islamic leadership and work motivation on employee performance used formula coefficient of determination (R2). From the test results the validity and reliability of the questionnaire, each grain revelation declared invalid, and the regression equation Y = 5.875 + 0.224 X1 + 0.637 X2 which means that any changes on the Islamic leadership (X1) and motivation (X2), the performance of employees will increased by 0.224 for the coefficients (X1) and 0.637 for the coefficient (X2). To test this hypothesis used tcount test for coefficient obtained 0.331 (X1), 3.670 for the coefficient (X2), this means that